Electroweak baryogenesis - Schmidt, Michael G. (Progress in particle and nuclear physics, 2011)
After a short general introduction to baryogenesis - the creation of a baryon asymmetry in our universe (BAU) - I will highlight some old and more recent models of electroweak baryogenesis: modifications of the Standard Model (SM), in particular supersymmetric ones as the MSSM, NMSSM, nMSSM, BMSSM, νμMSSM. I will also stress the role of electric dipole moments (EDMs) in limiting the CP violation needed for baryogenesis.